Narrative and graphic design of an online course: transferring skills from print publishing to the web. (1st January 2002) - Reilly, Andy; George, Alison
Educational publishing on the web raises new editorial and graphic design challenges. The Open University of the UK has for many years employed specialist editorial and graphic design support staff to help ensure quality standards in its print publishing operation. These support services are now being employed in the development of web-based learning materials. A large-scale course, T171: You, Your Computer and the Net, provides a case study in how issues of narrative design, written style and visual design on the web have been tackled.